PENGARUH SELF EFFICACY TERHADAP PERENCANAAN ARAH KARIER SISWA SMA DAN IMPLIKASINYA DALAM PELAYANAN BIMBINGAN KONSELING - Nengsih Nengsih (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2019)
Self efficacy is a person's belief in his ability to overcome various situations that arise in his life. The phenomenon that occurs adolescents have difficulty in planning and preparing for the future so that this responsibility is left to parents. This study aims to look at the effect of self efficacy on planning career paths of high school students and the implications in guidance and counseling services. This study uses descriptive inferencial method with a sample of 102 high school students in Stabat, selected by cluster sampling and random sampling. This study uses a Likert scale model. The results of this study indicate that there is an effect of self efficacy on planning career direction of high school students and the implications in the guidance and counseling service Keywords: Self efficacy, Career Direction Planning